Metabolically Engineered Extracellular Vesicles Released From a Composite Hydrogel Delivery System Regulate the Microenvironment for Periprosthetic Osteolysis Treatment - Chenchen Wang; Jiang Ju; Chao Fu; Bingbo Bao; Tianhui Ren; Yanan Li; Yuan Wang; Sheng Han; Yuan Wang; Xuan Huang; Hongxing Hu; Xianyou Zheng (Journal of Extracellular Vesicles, 2025)
ABSTRACT Despite remarkable progress in total joint arthroplasty, aseptic loosening of titanium (Ti) alloy persists as a critical clinical challenge due to the poor wear resistance and biological inertness of such implants. Targeting of inflammatory osteolysis and remodelling of the osseointegration environment represent promising therapeutic approaches to address this issue. In this study, we developed a novel engineered extracellular vesicles (EVs) with a tag of dextran sulfate (DS‐EVs) via metabolic glycan labelling (MGL)‐mediated click chemistry. This targeted delivery of EVs, derived from metabolically engineered stem cells, establishes a new cell‐free therapeutic system for periprosthetic osteolysis. DS‐EVs demonstrated specific macrophage tropism, effectively reprogramming macrophage polarisation from pro‐inflammatory M1 to regenerative M2 phenotypes. This phenotypic shift attenuated osteoclastogenesis while enhancing osseointegration through GPC6/Wnt pathway activation in vitro. Furthermore, we designed a multifunctional 3D titanium alloy scaffold with MXene‐PVA composite hydrogel coatings (Ti‐PPM scaffold). The multifunctional Ti‐PPM composite scaffold, incorporating DS‐EVs, provides a robust delivery system for periprosthetic osteolysis. This integrated system exhibits dual advantages of enhanced wear resistance and optimised interfacial adhesion, while enabling controlled EV release to maximize DS‐EVs' osseointegration potential in vivo. Collectively, our findings establish DS‐EVs as a transformative therapeutic modality for periprosthetic osteolysis through dual modulation of the osseointegration microenvironment and macrophage phenotypic heterogeneity.